Consumption of Cassava Extract (Manihot Esculenta) Improves Pancreatic Histology and Seminiferous Tubules in Wistar Rats Induced Diabetes Mellitus with Streptozotocin - Mohamad Rizki Adi Prasetyo; Qoit Muhammad Abdul Ghalib; Dwi Nur Ahsani; Ika Fidianingsih (Universitas Aisyah Pringsewu, 2023)
Diabetes Mellitus (DM) can damage various organs, which are the pancreas and the testes, which cause infertility. Therefore, alternative treatment is needed, including cassava (Manihot Esculenta) which contains polyphenol antioxidants that can reduce free radicals caused by hyperglycemia. The objectives of the study were to determine the effect of cassava consumption on the histological pancreas and testes of Wistar rats induced with streptozotocin. This study was an experimental study posttest only control group design. Experimental animals were divided into four treatment groups, namely healthy controls (K1), DM aqua dest (K2), DM metformin (K3), and DM cassava (K4). The treatment was given after successful DM induction. The histology of the pancreas was the area of the islets of Langerhans. The histology of the testes was the thickness of the seminiferous tubule epithelium. The analysis used a one-way ANOVA test. The average area of Langerhans Island, respectively, namely 6482,95±117.71 m2, 2597.49±137.25 m2, 2746.93± 172.07 m2, and 3307.00 ± 368.51 m2 (p-value = 0.000). The mean epithelial thickness of the seminiferous tubules was 19.62±1.12 m, 15.59 ±0.46m, 17.05±1.42m, and 18.09±0.52m (K4) (p-value = 0.000). In conclusion, the consumption of cassava extract (Manihot esculenta) can improve the histological picture of the pancreas and increase the thickness of the seminiferous tubule. Abstrak: Diabetes Mellitus (DM) dapat merusak berbagai organ yaitu pankreas dan testis yang menyebabkan kemandulan. Oleh karena itu, diperlukan pengobatan alternatif antara lain ubi kayu (Manihot Esculenta) yang mengandung antioksidan polifenol yang dapat meredam radikal bebas akibat hiperglikemia. Tujuan penelitian adalah untuk mengetahui pengaruh konsumsi singkong terhadap gambaran histologi pankreas dan testis tikus Wistar yang diinduksi dengan streptozotocin. Penelitian ini merupakan penelitian eksperimental post-test only control group design. Hewan coba dibagi menjadi empat kelompok perlakuan yaitu kontrol sehat (K1), DM aqua dest (K2), DM metformin (K3), dan DM singkong (K4). Perlakuan diberikan setelah induksi DM berhasil. Histologi pankreas yang akan diamati adalah area pulau Langerhans. Histologi testis adalah ketebalan epitel tubulus seminiferus. Analisis menggunakan uji one way ANOVA. Rata-rata luas Pulau Langerhans berturut-turut yaitu 6482,95±117,71 m2, 2597,49±137,25 m2, 2746,93 m2±172,07, dan 3307,00m2±368,51 (p-value = 0,000). Ketebalan epitel rata-rata tubulus seminiferus adalah 19.62±1.12m, 15.59±0.46 m, 17.05±1.42m, and 18.09±0.52 m (K4) (p-value = 0,000). Kesimpulannya, konsumsi ekstrak singkong (Manihot esculenta) dapat memperbaiki gambaran histologis pankreas dan meningkatkan ketebalan epitel tubulus seminiferus.